"Leading Many Sons to Glory": Historical Implications of Exclusive Language in the Epistle to the Hebrews - Peeler, Amy Lauren (Religions, 2021)
This study examined Hebrews’ use of gender-exclusive language for the purpose of understanding the author of the Epistle’s perspective on women and their role the religious community. The study used both broader historical research and exegetical analysis to support theological conclusions about Hebrews’ treatment of women. Despite the use of gender-exclusive language, the epistle does not suggest a bias against women. On the contrary, in the author of Hebrews’ hand, gendered language becomes a vehicle for understanding the implications of the gospel message for the Christian community.